One‐pot synthesis of the fluorocarbon quantum dots for sensitively detecting Fe3+. (1st May 2019) - Wang, Ning; Ai, Jun
Abstract : In this work, the novel method of generating fluorocarbon quantum dots (FQDs) in aqueous solution is demonstrated. The FQDs were synthesised by milk at high temperature and high‐pressure hydrothermal method, which were the only raw material. They synthesised high fluorescence, green FQDs. The Fe 3+ was added to FQDs, the fluorescence signal was quenched effectively. The fluorescence of FQDs showed a good linear relationship with the change of Fe 3+ concentration (50–700 μmol/l), and FQDs selected Fe 3+ to complete detection. Finally, the authors applied the prepared FQDs to the real samples to detect the Fe 3+ in the water. The iron ions belong to the Yellow River water, which is detected about 90.6–107%, and it is indicated that this method can be applied to detect iron ions in actual water samples. They successfully used milk to synthesis the FQDs, and it had high selectivity for Fe 3+ . So the authors' think the FQDs has great potential in the field.